Degradação dos fármacos ciprofloxacino e sertalina pelos processos ferro zero e foto-Fenton - aplicação em amostras de efluentes de estação de tratamento de esgoto - Perini, João Angelo de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In this work the degradation of the pharmaceuticals ciprofloxacin (CIP) and sertraline (SER) by zero-valent iron process (ZVI) and photo-Fenton process was evaluated. CIP degradation was also evaluated at low concentration for both degradation processes, with proportionately lower concentration of reagents. The degradation of the pharmaceuticals was studied in distilled water (DA) and the processes were further applied in two samples of sewage treatment plant effluent (STP) with different characteristics. Increase of the ZVI concentration from 1 to 5 g L-1 resulted in a sharp increase of the observed pseudo-first order rate constant (kobs) of CIP and SER degradation, tending to a plateau at around 10 g L-1. Smaller particles (200 mesh) resulted in a significantly lower degradation rate, compared to larger particles (20 mesh), attributed mainly to the generation of a high Fe2+ concentration (3.5 mM), resulting in scavenging of hydroxyl radicals (•OH). On the other hand, at low concentrations, the 200 mesh particle resulted in higher degradation of CIP. The contribution of adsorption to the overall removal of CIP and dissolved organic carbon (DOC) was higher than to SER. There was 88% of CIP removal, from which 37% was attributed to adsorption at pH 6.5 while COD was removed exclusively by this mechanism (78%). The presence of EDTA and other organic ligands improved the initial degradation rate. However, the final degradation percentage was similar for both pharmaceuticals. The fluoride generated corresponded to 34% of the theoretical value, indicating the presence of fluorinated degradation products, which was confirmed by the intermediaries determined by high performance liquid chromatography coupled to mass spectrometry. The degradation of the pharmaceuticals present in samples of STP effluents was analogous to that observed in distilled water, showing little influence of the matrix in degradation of CIP and SER by ZVI. The iron species...

Neste trabalho foi avaliada a degradação dos fármacos ciprofloxacino (CIP) e sertralina (SER) pelos processos ferro metálico (Fe0) e foto-Fenton com luz negra. A degradação de CIP também foi estudada em baixas concentrações pelos dois processos de degradação, cujas doses dos reagentes foram decrescidas proporcionalmente. A degradação dos fármacos foi estudada em água destilada (AD) e posteriormente os processos foram aplicados em duas amostras de estação de tratamento de efluentes (ETE) com características bastantes distintas. O aumento da concentração de Fe0 de 1 a 5 g L-1 resultou em aumento acentuado da velocidade de degradação inicial (kobs) de CIP e SER, tendendo a um patamar em 10 g L-1. As menores partículas (200 mesh) resultaram em velocidades de degradação menores para os fármacos quando comparadas às partículas de maior diâmetro (20 mesh), o que foi atribuído principalmente à alta concentração gerada de Fe2+ (3,5 mmol L-1), resultando no sequestro do radical hidroxila (•OH). Por outro lado, em baixas concentrações de Fe0, a partícula de 200 mesh resultou em maior degradação de CIP. As contribuições da adsorção na remoção de CIP e carbono orgânico dissolvido (COD) foram maiores em comparação a SER. Houve 88% de remoção de CIP dos quais 37% foi atribuído à adsorção em pH 6,5 enquanto que COD foi exclusivamente removido por este mecanismo (78%). A presença de EDTA e outros ligantes orgânicos aumentou a velocidade inical de degradação, entretanto, com porcentagem de degradação final dos fármacos semelhante. A geração de fluoreto corresponde a 34% do valor teórico, indicando a presença de intermediários fluorados de CIP, o que foi confirmado pelos intermediários determinados por cromatografia líquida de alta eficiência acoplada à espectrometria de massas. A degradação dos fármacos em amostras de efluentes de ETE foi similar à observada em água destilada...
Keywords: Quimica analitica; Fármacos; Ferro; Esgotos; Drugs